The Moral Aesthetics of Compulsory Ultrasound Viewing and the Theological Future of Abortion - Hovey, Craig (Studies in Christian ethics, 2019)
By law, women seeking abortions in some US states must undergo compulsory ultrasound viewing. This article examines the moral significance of this practice, especially as understood by pro-life religious groups, in light of Foucault's recently published lectures on 'The Will to Know' and the place of the aesthetic. How does the larger abortion-debate strategy of 'showing' and 'seeing' images-whether of living or dead fetuses-work as an aesthetic form of argument that intends to evoke a moral response in the absence of reason-giving? The article draws on recent, parallel debates regarding disgust before concluding with a theological response to the priority of will over knowledge and vision over action as commentary on the future of abortion debate and law, especially in the United States.